The Role of Corporate Social Responsibility (CSR) of PT Pertamina Indonesia in Community Empowerment Through Free Education Initiatives - Nisa, Cholifatun; Bayangkara, Ida Bagus Ketut (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study explores the role of PT Pertamina’s Corporate Social Responsibility (CSR) in empowering communities through free education initiatives. The focus lies on scholarship programs such as Sobat Bumi and Sekolah Energi Berdikari, aimed at underprivileged students. A descriptive qualitative method was used, based on secondary data from PT Pertamina’s sustainability reports from 2021 to 2023. The findings reveal that these programs significantly enhance educational access and create broad positive impacts on surrounding communities. Pertamina’s CSR efforts have proven effective in improving human resource quality and supporting inclusive and sustainable social development.